A Journey Through Education Today. Changes Required - Zuleyka Suárez Valdés-Ayala (Universidad Nacional, Costa Rica, 2011)
This essay aims at raising awareness on the changes required in Education to continuously search for quality improvement and the formation of integral human beings. Eight fundamental aspects are included in this paper. Such aspects need to be applied in the short- or medium term to have a significant progress, keeping in mind that the change must be permanent.